ПРОГНОЗИРОВАНИЕ ТРАНСФОРМАЦИИ РЕЦИДИВИРУЮЩЕЙ ФОРМЫ ФИБРИЛЛЯЦИИ ПРЕДСЕРДИЙ В ХРОНИЧЕСКУЮ У ПАЦИЕНТОВ С АРТЕРИАЛЬНОЙ ГИПЕРТОНИЕЙ - Н. Е. Григориади; Л. М. Василец; А. В. Туев; А. В. Петруша; Е. А. Ратанова (SINAPS LLC, 2014)
To evaluate the prognostic significance of markers of fibrosis in the risk of transition persistent atrial fibrillation in chronic form. It was revealed that the performance of remodeling of the left atrium (the level of PICP, TIMP-1, and the index of the PL to the BSA) have predictive value in the risk of progression of AF. The risk of transition to a chronic form of arrhythmia increases as the concentration of PICP over 133 ng/ml (Se 70-73% and Sp 62-75%), at a concentration of TIMP-1 less than 490 ng/ml (Se 67-78%, Sp 69-75%) and index of LP to PPT than 32-34 ml/m 2 (Se 80%, Sp 77-83%). For patients with AF against hypertension risk relapsing forms of transition to permanent AF occurs when the level of PICP over 151 ng/ml (1.01 fold increases in each of the subsequent increase in the concentration of 1 ng/ml) and the value of the index volume ma LP PPT to over 38 ml/m 2 (by 1.5 times for each subsequent increase of 1 ml/m2).